STRATEGI PEMASARAN MELALUI PENERAPAN DIGITAL MARKETING PADA UMKM SYAQILA FLOWER - Putri Najwa Safitri; Hera Wati; Laras Fitri Aini Hasibuan; Irene Checilia Sihotang; Hendra Saputra (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to analyze marketing strategies through the implementation of digital marketing at Syaqila Flower, an SME engaged in the sale of flowers and ornamental plants in Medan, North Sumatra. This research is expected to enhance knowledge about effective marketing strategies for SMEs in the digital era. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The informant in this study is the owner of Syaqila Flower. The results show that Syaqila Flower uses Facebook as the main platform for digital marketing, displaying photos and videos of products, including prices, and promoting products. Social media has proven to be effective for marketing as it is not limited by distance and time. Additionally, Syaqila Flower collaborates with third parties. Although effective, there are several areas for improvement, such as the use of influencers, collaboration with other parties, and improving the quality of content on marketplaces. This study shows that digital marketing can be an effective strategy to increase sales and reach a wider range of consumers for SMEs in the digital era.